Subjective Representation of Complexity - Nabil I. Al-Najjar; Ramon Casadesus-Masanell; Emre Ozdenoren (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
We study how individuals cope with the complexity of their environment by developing subjective models, or representations, to guide their predictions and decisions. Formally, an individual who believes his environment is deterministic, but too complex to permit tractable deterministic representation, builds a probablistic model embodying perceived regularities of that environment. In this model, the individual's inability to think through all possible instances of the problem is represented by an uncertainty about random states. The resulting behavior is fully rational in the traditional sense, yet consistent with an agent who believes his environment is too complex to warrant precise planing, forgoes finely detailed contingent rules in favor of vaguer plans, and expresses a preference for flexibility. We consider applications to time-inconsistent preferences, delegation, and two-player simultaneous games.
Keywords: 330